Perspectives of development of trade and economic relations between Ukraine and Canada on the modern stage - Vodopyanova, Yevgeniya (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The paper purpose is to study the relevance of the deepening of cooperation between Canada and Ukraine, given the decisive role of the signing of a free trade agreement between countries in the development of the economy of Ukraine. Design/methodology/approach. The basic principles of the research are the historical, systemic and comparative methods used by the institutional and structural-functional approaches. Findings. The subject of research is the theoretical, methodological and applied aspects of the development of integration processes, historical analysis and the evolution of the formation of diplomatic relations between countries. Research limitations/implications. The scientific significance of the work lies in the study of the process of economic cooperation between states and the implementation of joint projects, taking into account the peculiarities of the development of economic policy in Ukraine. As a conclusion, the ways of development of trade and economic relations between Ukraine and Canada are given with the introduction of current proposals for changes. Originality/value. The importance of highlighting the prospects for the development of trade and economic relations between Ukraine and Canada, as well as further development of progressive model of cooperation, are valuable. Further research will contribute to the modernization of the Ukrainian economy, which will open up new opportunities for international economic activity and deepening cooperation, as well as creation the conditions for the implementation of the latest technologies and interaction within a single global economy.